Prediction of Pulmonary Arterial Hypertension in Chronic Obstructive Lung Disease from Three‐Dimensional Vectorcardiographic Parameters. Issue 3 (28th September 2015) - Pan, Dianzhu; Liu, Renguang; Ren, Shuzhen; Li, Changjun; Chang, Qinghua
Abstract : Aim: The objective of our study was to assess diagnostic value of three‐dimensional (3D) vectorcardiographic (VCG) parameters in detecting pulmonary arterial hypertension (PAH) in chronic obstructive lung disease (COLD) with and without right ventricular hypertrophy (RVH). Methods: The study group of 62 patients with COPD was stratified on the basis of color Doppler echocardiographic findings into three subgroups: non‐PAH (n = 23), PAH without RVH (n = 22), and PAH with RVH (n = 17). Pairwise differences between the subgroups were evaluated by one‐way analysis of variance, and Pearson correlation analysis was used to evaluate the significance of the correlations between pulmonary arterial systolic pressure (PASP) and various VCG parameters. Results: The azimuth of the QRS vector decreased from −24° in the non‐PAH group to −62° in PAH without RVH and to −140° in PAH with RVH (P < 0.01 for pairwise differences between all three groups). Similar significant decrease was observed for the azimuth of the ventricular gradient (VG) vector. Spatial QRS/T angle increased from 69° in the non‐PAH group to 115° in PAH without RVH (P < 0.01). In the PAH group with RVH, QRS/T angle was 94° (P < 0.05 for difference from the non‐PAH group). There was a significant correlation between PASP and QRS/T angle (r = 0.89, P < 0.05) and between PASP and the azimuth of the VG vector (r = 0.86, P < 0.05). PASP increase from linear regression model was 0.8 mmHg for a QRS/T angle increase by 10° and 1.3 mmHg for each 10° increase in the azimuth of the VG vector. Conclusion: 3DVCG parameters are potentially useful for predicting PASP in COLD patients, and possibly also for differentiation between COLD patients with PAH and RVH from those without RVH.